2018
DOI: 10.21891/jeseh.436730
|View full text |Cite
|
Sign up to set email alerts
|

The Relationships between Parental Involvement, Students’ Basic Psychological Needs and Students’ Engagement in Science: A Path Analysis

Abstract: This article may be used for research, teaching, and private study purposes. Any substantial or systematic reproduction, redistribution, reselling, loan, sub-licensing, systematic supply, or distribution in any form to anyone is expressly forbidden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
6
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 25 publications
4
6
0
2
Order By: Relevance
“…Similar results were obtained among Taiwanese students, whose experience of need satisfaction was positively correlated to both general self-efficacy and science learning self-efficacy (Wang and Tsai, 2020). In fact, need satisfaction could significantly predict students' learning engagement, which explained more than 70% of variance (Kurt and Tas, 2018).…”
Section: Psychological Needs and Behavior Regulation In Learning And ...supporting
confidence: 74%
“…Similar results were obtained among Taiwanese students, whose experience of need satisfaction was positively correlated to both general self-efficacy and science learning self-efficacy (Wang and Tsai, 2020). In fact, need satisfaction could significantly predict students' learning engagement, which explained more than 70% of variance (Kurt and Tas, 2018).…”
Section: Psychological Needs and Behavior Regulation In Learning And ...supporting
confidence: 74%
“…Providing guidance and advice makes children have ideals; providing supervision over their learning is to provide motivation and rewards so that children are encouraged to learn and excel, while the fulfillment of the facilities needed in learning is so that children are more firmly established in an idealism to be achieved by utilizing available facilities there is. The forms of parental participation in the development of children's achievements include: Giving encouragement to children about the importance of education for their children's future, as a facilitator for all children's activities, being a source of knowledge and knowledge in the family, motivating children to continuously improve learning achievement they, as a place to ask questions and complain about things that are children's problems, provide clear directions for their children's future (Kurt & Taş, 2018;Rajendran et al, 2020).…”
Section: Counseling For Studentsmentioning
confidence: 99%
“…In the reviewed studies, the classroom environment was addressed through the aspects of basic psychological needs fulfilment following SDT. Some studies reported a positive association of student basic psychological needs variable with dimensions of engagement (Kurt & Tas, 2018;Tas, 2016;Molinari & Mameli, 2018). Kurt and Tas (2018) revealed that parental involvement (high educational aspiration, parental communication, parental participation, and parental autonomy support) predicted satisfaction of basic psychological needs of students at school.…”
Section: Figure 1 Constructs Associated With Engagement and Agentic E...mentioning
confidence: 99%
“…Some studies reported a positive association of student basic psychological needs variable with dimensions of engagement (Kurt & Tas, 2018;Tas, 2016;Molinari & Mameli, 2018). Kurt and Tas (2018) revealed that parental involvement (high educational aspiration, parental communication, parental participation, and parental autonomy support) predicted satisfaction of basic psychological needs of students at school. A special focus lay on the reciprocity of student engagement and teacher autonomy support.…”
Section: Figure 1 Constructs Associated With Engagement and Agentic E...mentioning
confidence: 99%